RELIGIOUS EMPOWERMENT THROUGH MAJELIS TAKLIM: ISLAMIC LEARNING STRATEGY FOR MIGRANTS - Sugianto, Hendi; Karim, Abdul rahim; Rofiqi, Rofiqi; Khoiriyah, Siti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research examines the role of majlis taklim in Islamic religious learning for migrants in Ternate City, focusing on applying the andragogy approach. Majelis Taklim serves as an informal space to strengthen the spiritual identity of migrants separated from their home environment. Through participatory and experiential approaches, majlis tackle provides flexibility in learning that allows the congregation to understand Islamic teachings applicable to daily life. This research uses a qualitative method with a phenomenological approach. The data collection techniques in the study include observation, in-depth interviews, and documentation to collect data from several taklim assemblies in Ternate City, namely Majelis Taklim Walisongo, Jum'at Wage, Lailatul Iltima', and Jawara. The research findings indicate that majelis taklim are instrumental in preserving the religious identity of migrants, enhancing social connections, and offering worshipers the chance to deepen their spiritual understanding of the challenges they face in their lives. While this study focuses on a limited number of majelis taklims in Ternate City, the results contribute to the broader comprehension of experiential Islamic learning within migrant communities.Keywords:   Andragogy, Islamic Religious Learning, Majelis Taklim, Migrants, Religious Identity.